Acute effects of the resistance exercise associated with different blood flow restriction pressures on bone remodeling biomarkers - Sedinei Lopes Copatti; Sabrina Lencina Bonorino; Anieli da Costa Copatti; Chrystianne Barros Saretto; Fernando Schorr Grossl; Marzo Edir Da Silva-Grigoletto; Vanessa da Silva Corralo; Clodoaldo Antônio De Sá (Elsevier, 2022)
Background/Objectives: The present study analyzed the acute responses of parathyroid hormone (PTH) and bone-specific alkaline phosphatase (BSAP) to the low-intensity resistance exercise with blood flow restriction using different occlusion pressures. Methods: Twelve women completed the three protocols of this crossover study: resistance exercise without blood flow restriction (RE), resistance exercise with blood flow restriction and occlusion pressure corresponding to 70% of systolic blood pressure (RE + BFR70), and resistance exercise with blood flow restriction and occlusion pressure corresponding 130% of systolic blood pressure (RE + BFR130). All exercises were performed in a guided squat apparatus with load corresponded to 30% of one-repetition maximum test. Results: Relative to resting levels, PTH concentrations decreased significantly (p = .000) post-exercise in all groups and increased significantly (p = .000) 15 min post-exercise in RE + BFR70 and RE + BFR130 groups; PTH concentrations returned to resting levels after the 30-min recovery period in all groups. There was no significant difference (p >.05) between BSAP values at rest and 30 min post-exercise. Conclusion: In conclusion, our results showed that protocols with blood flow restriction using occlusion pressures equivalent to 70% and 130% of systolic blood pressure were more effective than RE alone to induce PTH peaks, and to promote a metabolic condition favorable to bone anabolism.